Connie Hagar : the life history of a Texas birdwatcher - McCracken, Karen Harden, 1905- (Texas A & M University Press, 1986)
"In any other context, saying that someone was "for the birds" would hardly be polite. But applied to Connie Hagar, it would be high praise. The diminutive birdwatcher nick-named Connie was reared as Martha Conger Neblett in early twentieth-century Texas, where she led a genteel life of tea parties and music lessons. But at middle age she became fascinated with birds and resolved to learn everything she could about them. In 1935, she and her husband, Jack, moved to Rockport, on the Coastal Bend of Texas, to be at the center of one of the most abundant areas of bird life in the country. Her diligence in observation soon had her setting elite East Coast ornithologists on their ears, as she sighted more and more species the experts claimed she could not possibly have seen. (Repeatedly she proved them wrong.) She ultimately earned the respect and love of birders from the shores of New Jersey to the islands of the Pacific. Life magazine pictured her in a tribute to the country's premier amateur naturalists, and she received many awards from nature and birding societies."--Jacket